2013
DOI: 10.5114/fn.2013.34190
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of neuropathological changes in Alzheimer’s disease: a review

Abstract: , , V Vl la ad di im mí ír r J Ja an no ou ut t

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
82
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(91 citation statements)
references
References 75 publications
1
82
0
8
Order By: Relevance
“…This concept is supported by the findings of Strickland and his group, who have shown that persistent fibrin deposits contribute to neuro-inflammation [3]. In conclusion, we believe that the information presented above supports arguments presented by Serý et al [6] that deserve further attention.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…This concept is supported by the findings of Strickland and his group, who have shown that persistent fibrin deposits contribute to neuro-inflammation [3]. In conclusion, we believe that the information presented above supports arguments presented by Serý et al [6] that deserve further attention.…”
supporting
confidence: 80%
“…In their review article Serý et al [6] have presented compelling arguments in favour of the role of vascular mechanisms in the development of Alzheimer's disease (AD). These arguments are in line with a recent series of publications questioning the prevailing concept of amyloid beta-induced neurodegeneration.…”
mentioning
confidence: 99%
“…Alzheimer's disease (AD) is characterized both clinically by the decline of cognitive functions, such as memory, and pathologically by the presence of numerous senile plaques (SPs) and neurofibrillary tangles (NFTs) [2,3,28,40,46,51]. Neurofibrillary tangles consist of hyperphosphorylated tau protein, whereas Folia Neuropathologica 2014; 52/1 Trp53 and p53 in PS/APP mice SPs are composed of amyloid β-protein (Aβ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the increased inclusion of exon 10 in transcripts show an imbalance in the 3R and 4R tau isoforms [2,9,15]. The ratio of these two isoforms in normal condi tions is generally equal (1 : 1), but it varies depend ing on the type of mutation [24]. Corticobasal degen eration (CBD) is characterized by increased 4R tau, whereas frontotemporal lobar degeneration with Pick bodies shares an overabundance of 3R tau (Fig.…”
Section: Discussionmentioning
confidence: 99%